Intracardiac thrombus in children with dilated cardiomyopathy - Ahmet İrdem; Osman Başpınar; Mehmet Kervancıoğlu; Metin Kılınç (KARE Publishing, 2014)
Objectives: The risk of fatal pulmonary and systemic thromboembolism is high in patients with dilated cardiomyopathy with cardiac thrombus. This study was planned to reveal the efficacy of antiaggregant therapy in patients with low left ventricular systolic ejection fraction (LVEF). Study design: The present study retrospectively reviewed the files of 83 cases (42 males, 41 females) with dilated cardiomyopathy who were followed between June 2004 and December 2011. Results: Intracardiac thrombus was detected in five (6%) cases; of these five patients, dilated cardiomyopathy was idiopathic in four and secondary to chronic renal failure in one. The cases were followed for a mean of 33.6+-35.6 months (3 days-168 months). Mean LVEF on transthoracic echocardiography was found as 35.2+-2.7% (32-38%) for the cases with intracardiac thrombus, whereas it was 34.7+-11.0% (10-55%) for the cases without intracardiac thrombus. No statistically significant difference was found between the groups (p=0.910). Cases with LVEF ≤30% were routinely receiving acetylsalicylic acid at antiaggregant dose. Conclusion: We think that prophylactic antithrombotic/antiaggregant therapy should be started at the time of diagnosis even in patients with LVEF >30%, as thrombus development was seen in cases with LVEF >30% without any antiaggregant therapy.